Study on Performance Polyurethane Cellular Foam (PUC) Block as Ground Improvement by Analysis Using Plaxis 2D - Azhar, Aina Ilyana; Yahya, Nur Faezah (Progress in Engineering Application and Technology, 2024)
Immediate settlement, also known as initial or undrained settlement, occurs as soon as a load is applied is a common problem in road embankment construction, resulting in uneven surfaces, impaired structural integrity, and higher maintenance costs. This study uses the finite element method (FEM) software PLAXIS 2D to forecast road settlement behaviour and investigates the usage of Polyurethane Cellular Foam (PUC) Block as a ground improvement strategy. To simulate the real conditions of road embankments, the earth-fill embankment's settlement will be applied as a control analysis to determine the characteristics that will eventually be compared with the embankment with the PUC block. Three totally different PUC block arrangements were applied during a simulation. Thus, after determining the optimal arrangement technique, two different thicknesses were used to minimize settlement value comparison data. Three types of data collection were used as guidelines for the parameter data. The results of the analysis showed that PUC block is a useful technique for reducing the influence of road embankments on settlement on soft soil. Finally, it is determined that the road embankments can effectively use PUC block as ground improvement.